Entübe yoğun bakım hastalarında pozisyon verme ve aspirasyon sırasındaki ağrı düzeylerinin iki farklı ağrı ölçeği ile değerlendirilmesi - Yağız, Rabia (My University, 2019)
Amaç: Entübe yoğun bakım hastalarında pozisyon verme ile aspirasyon sırasındakiağrı düzeylerinin “Yoğun Bakım Ağrı Gözlem Ölçeği (YBAGÖ)” ve “DavranışsalAğrı Ölçeği (DAÖ)” ile değerlendirmek ve hangisinin en yüksek geçerlik vegüvenirliğe sahip olduğunu belirlemektir.Yöntem: Prospektif gözlemsel bir kohort çalışması olan bu araştırmada basit rastgaleörneklem yöntemiyle belirlenen 112 entübe hastanın demografik ve kliniközelliklerine ilişkin veriler “Veri Toplama Formu”na kaydedilirken, pozisyon vermeve aspirasyondan 1 dakika önce, sırası ve 20 dakika sonra toplamda 672 kere ağrıdüzeyleri eş zamanlı olarak “DAÖ” ve “YBAGÖ” ile değerlendirildi ve “Hasta İzlemFormu”na kaydedildi. Ölçeklerin iç tutarlığı Cronbach alpha katsayısı, ayırd edicigeçerlikleri Wilcoxon signed rank test ve Pearson korelasyon analizi, duyarlılıklarıeffect size testi ile değerlendirildi.Bulgular: DAÖ ve YBAGÖ puan ortalamaları aspirasyon sırasında 2 puanlık,pozisyon sırasında 1 puanlık anlamlı bir artış gösterdi. Her iki işlem öncesi, sırası vesonrası ölçekler birbirleriyle pozitif yönde ilişkiliydi (p<0,001). Aspirasyon vepozisyon verme sırasında Cronbach alpha değerleri sırasıyla DAÖ’nin 0,82 ve 0,80(p=0,99); YBAGÖ’nin 0,83 ve 0,81 (p=0,15) olarak saptandı. Aspirasyon ve pozisyonverme sırasında etki büyüklükleri ise sırasıyla YBAGÖ’nin 1,331 ve 0.770, DAÖ’nin1,288 ve 0.657 idi.Sonuç: Çalışma bulguları klinik kullanımda her iki ölçeğin de geçerli ve güvenilirolduğunu gösterdi. Bununla birlikte YBAGÖ’nün duyarlığı daha yüksek olduğundanbu hasta grubunda, özellikle etki büyüklüğü göz önüne alınarak, YBAGÖ daha tercihedilir görünmektedir.

Aim: The aim of the study is to assess the pain levels of intubated intensive care patients withpositioning and aspiration during positioning and aspiration operations with the help of“Critical Care Pain Observation Tool” and Behavioral Pain Assessment Scales” and todetermine which one has the highest validity and reliability.Method: In this prospective observational study, while data related to demographic andclinical features of the 112 intubated patients determined through simple randomized samplingmethod were recorded in “Data Collection Form” their pain levels were assessed with the helpof Critical Care Pain Observation Tool and Behavioral Pain Assessment Scales 1 minutebefore data collection form, positioning and aspiration operations, during the operation and 20minutes after the operation in total of 672 times and recorded into Patient Follow-Up Form.Internal consistency of the scales, Cronbach Alpha Coefficient, discriminant validities wereassessed through Wilcoxon Signed Rank Test and Pearson Correlation Analysis, theirsensitivities were evaluated through Effect Size Test.Findings: The mean scores of Behavioral Pain Assessment Scales and Critical Care PainObservation Tool showed a significant increase of 2 points during the aspiration and showed1 point during the positioning proces. Both scales were positively correlated with each otherbefore, during and after the operation (p<0,001). Cronbach alpha values were found to be 0,82and 0,80 (p=0,99) in Behavioral Pain Assessment; and in Critical Care Pain Observation Toolthey were found to be 0,83 and 0,81 (p=0,15) respectively. The effect size of Critical CarePain Observation Tool during aspiration was 1.331 and 0.770 during positioning, while theeffect size of Behavioral Pain Assessment Scales was 1.288 during aspiration and 0.657 duringpositioning.Conclusion: YBAGÖ showed a better effect size than the WAD scale in both procedures.Aspiration scores were higher and statistically significant in both scales than positioning.
Keywords: Ağrı; aspirasyon; aspiration; Hastalar; hemşire; Hemşirelik; Intensive care; nurse; Nursing; Patients; position; pozisyon pain; Yoğun bakım